Identification and verification of hub genes associated with the progression of non-small cell lung cancer by integrated analysis - Mengyan, Xie; Kun, Ding; Xinming, Jing; Yutian, Wei; Yongqian, Shu (Frontiers in Pharmacology, 2022)
Objectives: Lung cancer is one of the most common cancers worldwide and it is the leading cause of cancer-related mortality. Despite the treatment of patients with non-small cell lung carcinoma (NSCLC) have improved, the molecular mechanisms of NSCLC are still to be further explored. Materials and Methods: Microarray datasets from the Gene Expression Omnibus (GEO) database were selected to identify the candidate genes associated with tumorigenesis and progression of NSCLC. The differentially expressed genes (DEGs) were identified by GEO2R. Protein-protein interaction network (PPI) were used to screen out hub genes. The expression levels of hub genes were verified by GEPIA, Oncomine and The Human Protein Atlas (HPA) databases. Survival analysis and receiver operating characteristic (ROC) curve analysis were performed to value the importance of hub genes in NSCLC diagnosis and prognosis. ENCODE and cBioPortal were used to explore the upstream regulatory mechanisms of hub genes. Analysis on CancerSEA Tool, CCK8 assay and colony formation assay revealed the functions of hub genes in NSCLC. Results: A total of 426 DEGs were identified, including 93 up-regulated genes and 333 down-regulated genes. And 9 hub genes (CDC6, KIAA0101, CDC20, BUB1B, CCNA2, NCAPG, KIF11, BUB1 and CDK1) were found to increase with the tumorigenesis, progression and cisplatin resistance of NSCLC, especially EGFR- or KRAS-mutation driven NSCLC. Hub genes were valuable biomarkers for NSCLC, and the overexpression of hub genes led to poor survival of NSCLC patients. Function analysis showed that hub genes played roles in cell cycle and proliferation, and knockdown of hub genes significantly inhibited A549 and SPCA1 cell growth. Further exploration demonstrated that copy number alterations (CNAs) and transcription activation may account for the up-regulation of hub genes. Conclusion: Hub genes identified in this study provided better understanding of molecular mechanisms within tumorigenesis and progression of NSCLC, and provided potential targets for NSCLC treatment as well.